Tremor, olfactory and motor changes in Italian adolescents exposed to historical ferro-manganese emission - Lucchini, Roberto G.; Guazzetti, Stefano; Zoni, Silvia; Donna, Filippo; Peter, Stephanie; Zacco, Annalisa; Salmistraro, Marco; Bontempi, Elza; Zimmerman, Neil J.; Smith, Donald R. (Neurotoxicology (Park Forest South), 2012)
Increased prevalence of Parkinsonism was observed in Valcamonica, Italy, a region impacted by ferroalloy plants emissions containing manganese and other metals for a century until 2001. The aim of this study was to assess neurobehavioral functions in adolescents from the impacted region and the reference area of Garda Lake. Adolescents age 11–14 years were recruited through the school system for neuro-behavioral testing. Metals including manganese, lead, iron, zinc, copper were measured in airborne particulate matter collected with 24-h personal samplers, and in soil, tap water, blood, urine and hair. Independent variables included parental education and socio-economic status, children's body mass index, number of siblings, parity order, smoking and drinking habits. A total of 311 subjects (49.2% females), residing in either the exposed (n=154) or the reference (n=157) area participated. Average airborne and soil manganese were respectively 49.5ng/m3 (median 31.4, range 1.24–517) and 958ppm (median 897, range 465–1729) in the impacted area, and 27.4ng/m3 (median 24.7, range 5.3–85.9) ng/m3 and 427ppm (median 409 range 160–734) in the reference area. Regression models showed significant impairment of motor coordination (Luria-Nebraska test, p=0.0005), hand dexterity (Aiming Pursuit test, p=0.0115) and odor identification (Sniffin’ task, p=0.003) associated with soil manganese. Tremor intensity was positively associated with blood (p=0.005) and hair (p=0.01) manganese. Historical environmental exposure to manganese from ferroalloy emission reflected by the concentration in soil and the biomarkers was associated with sub-clinical deficits in olfactory and motor function among adolescents.